2023
DOI: 10.1002/oby.23663
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in response to lifestyle intervention among children and adolescents: Systematic review and meta‐analysis

Abstract: Objective: Little is known about sex differences in response to lifestyle interventions among pediatric populations. The purpose of this analysis was to evaluate sex differences in adiposity following lifestyle interventions among children and adolescents with overweight or obesity aged 6 to 18 years old. Methods: Searches were conducted in PubMed, Web of Science, and MEDLINE (from inception to March 2021), and references from included articles were examined. Eligibility criteria included children and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
(418 reference statements)
0
2
0
Order By: Relevance
“…22 However, a recent systematic review found no significant differences between boys and girls in any of the body composition measures, including weight, BMI, BMI z-score, percentage body fat and waist circumference. 23 In the Gulf region specifically, Choudhury et al 24 reported no gender differences in BMI or other body composition measures. Similarly, in a school-based intervention conducted in Kuwait, there was no significant gender difference in participants’ BMI change.…”
Section: Discussionmentioning
confidence: 98%
“…22 However, a recent systematic review found no significant differences between boys and girls in any of the body composition measures, including weight, BMI, BMI z-score, percentage body fat and waist circumference. 23 In the Gulf region specifically, Choudhury et al 24 reported no gender differences in BMI or other body composition measures. Similarly, in a school-based intervention conducted in Kuwait, there was no significant gender difference in participants’ BMI change.…”
Section: Discussionmentioning
confidence: 98%
“…A multidisciplinary inpatient program carried out in Switzerland in a small group of adolescents with severe obesity, showed that boys lowered their BMI by a greater extent than girls ( 28 ). A recent review analyzed the effect of gender on response to lifestyle intervention among children and adolescent and concluded that boys and girls did not demonstrate a differential response to the treatment for weight, BMI z score or waist circumference ( 29 ). Most of the study included in this review was not designed to detect sex as a primary determinant of outcomes.…”
Section: Discussionmentioning
confidence: 99%